ISOLATION, IDENTIFICATION AND ANALYSIS OF SHORT INTERSPERSED NUCLEAR ELEMENT (SINE) FROM VARANUS KOMODOENSIS - Widya Asmara (Jurnal Sain Veteriner, 1999)
All vertebrata genomes studied so far contain SINEs, that consti tute up to 5% of the total genome. Most of the SINE sequences studied so far are mammalian genomes. There Is very limited information about SINE sequences from reptiles, especially of Varanus family.Isolation of SINE sequences were carried out by constructing the komodo genomic library in E. coli. Suspected positive clones were detected by genome to genome hybridization. The SINE sequences identification were carried out by enzymatic method, and the DNA sequences were analysed with the GENETYX-SV program-Up to now there are 2 SINE sequences from komodo genome have been isolated and identified. Their sequences homo logy is 85-2% From Database search analysis with the GenBank indicated that those SlNEs were not evolved from any specific tRNA gene.